2016
DOI: 10.1002/jnr.23815
|View full text |Cite
|
Sign up to set email alerts
|

Stress, sex, and motivated behaviors

Abstract: Stress is a major risk factor for the development of psychiatric disorders, such as depression, and the development of substance use disorder. Although there are important sex differences in the prevalence of these disorders, the majority of preclinical models used to study stress induced disorders use males only. Social defeat stress is a commonly used method to induce stress in an ethologically relevant way, but has only recently begun to be used in female rodents. Using these new female models, recent studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 84 publications
(155 reference statements)
2
19
0
Order By: Relevance
“…Our results are consistent with a vast literature showing that stressors alter the mesolimbic DA pathway and DA-mediated behaviors (Cabib and Puglisi-Allegra, 1996; Cao et al, 2010; Chaudhury et al, 2013; Di Chiara et al, 1999; Fone and Porkess, 2008; Imperato et al, 1992; Kalivas and Duffy, 1995; Krishnan et al, 2007; Laman-Maharg and Trainor, 2017; Tidey and Miczek, 1996; Valenti et al, 2012). For example, animals who experience early life stress exhibit behavioral hyperactivity in response to DA agonists (Brake et al, 2004; Lovic et al, 2006; Matthews and Robbins, 2003), suggesting stress induces a hyperdopaminergic state.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are consistent with a vast literature showing that stressors alter the mesolimbic DA pathway and DA-mediated behaviors (Cabib and Puglisi-Allegra, 1996; Cao et al, 2010; Chaudhury et al, 2013; Di Chiara et al, 1999; Fone and Porkess, 2008; Imperato et al, 1992; Kalivas and Duffy, 1995; Krishnan et al, 2007; Laman-Maharg and Trainor, 2017; Tidey and Miczek, 1996; Valenti et al, 2012). For example, animals who experience early life stress exhibit behavioral hyperactivity in response to DA agonists (Brake et al, 2004; Lovic et al, 2006; Matthews and Robbins, 2003), suggesting stress induces a hyperdopaminergic state.…”
Section: Discussionsupporting
confidence: 93%
“…However, depression and anxiety are more common in women than men [22] and sex differences in physiological responses to stress are an important risk factor [23-25]. Shershen et al [26] showed that the KOR agonist U62,066 potentiated cocaine-induced locomotor activity in female mice during the first 20 minutes of testing, but this difference dissipated over the next hour.…”
Section: Introductionmentioning
confidence: 99%
“…This allowed us to observe the effects of social defeat stress in males, as well as females. In California mice, three episodes of social defeat induced social aversion in females but not males [25, 31, 32]. We used a place aversion assay to quantify the aversive properties of the KOR agonist U50,488 and to determine whether social defeat stress has different effects on aversion in males and females.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The connectivity of the bilateral BNST (or sometimes BST) is extensive and far-reaching-the BNST is interconnected with the amygdala, dorsal raphe, hippocampus, hypothalamus, medulla, nucleus accumbens, periaqueductal gray, prefrontal cortex, thalamus, ventral tegmental area, among others (for recent reviews, see Avery et al 2016;Lebow and Chen 2016). As a result of this connectivity, it is perhaps not surprising that the BNST has been implicated in a number of functions and behaviors relevant to psychiatric disorders, including the acquisition and expression of Pavlovian fear conditioning, reinstatement of drug seeking, negative affect in pain, compulsivity, the expression of social defeat and learned helplessness, social attachment and reproductive behaviors, and regulation of the stress axis (Davis et al 2010;Hammack et al 2012;Crestani et al 2013;Petrulis 2013;Adhikari 2014;Coria-Avila et al 2014;Stamatakis et al 2014;Takahashi 2014;Fox et al 2015;Kash et al 2015;Minami and Ide 2015;Avery et al 2016;Daniel and Rainnie 2016;Gungor and Paré 2016;Lebow and Chen 2016;Mantsch et al 2016;Waraczynski 2016;Laman-Maharg and Trainor 2017;Vranjkovic et al 2017). Moreover, a growing body of research links BNST function (and its dysfunction) to a number of human pathological disorders such as anxiety and addiction (Fox et al 2015;Avery et al 2016;Lebow and Chen 2016)-disorders that are widespread, extremely costly to the individual, and often comorbid (Kessler et al 2005a,b;Koob 2009;McEwen 2012;Whiteford et al 2013; DiLuca and Olesen 2014; Gonzalez and Martinez 2014).…”
mentioning
confidence: 99%